Τhe Effects οf Reciprocal and Self–Check Teaching Styles in Intrinsic–Extrinsic Motivation and Lesson Satisfaction in Physical Education - Mizios Δημήτριος; Diggelidis Νικόλαος; Goudas Μάριος; Papaioannou Αθανάσιος (Inquiries in Physical Education and Sport, 2009)
The purpose of the present study was to investigate the effects of the implementation of two different teaching styles on students’ motivation, lesson satisfaction and their performance in three basketball skills: chest-pass, dribbling, and jump shot. One hundred and six junior high school students (57 boys and 49 girls) aged 12 years old (Μ=12.03±.21) participated in this survey which was held through motor tests and questionnaires. Three groups (including the control group) of students were assigned into two teaching styles: the reciprocal and the self–check style. All scales had acceptable levels of internal consistency. Self–check style group had higher scores concerning intrinsic motivation and identified regulation compared with reciprocal style groups, while reciprocal style group had higher scores concerning autonomy. Overall, both genders improved significantly their performances in all basketball skills, even though boys showed higher scores. Therefore, the indications are that the more pupil-centered teaching styles have a positive influence on children’s motor improvement and motivation towards P.E.